2016
DOI: 10.1152/ajprenal.00360.2015
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin/V2 receptor stimulates renin synthesis in the collecting duct

Abstract: Renin is synthesized in the principal cells of the collecting duct (CD), and its production is increased via cAMP in angiotensin (ANG) II-dependent hypertension, despite suppression of juxtaglomerular (JG) renin. Vasopressin, one of the effector hormones of the reninangiotensin system (RAS) via the type 2-receptor (V2R), activates the cAMP/PKA/cAMP response element-binding protein (CREB) pathway and aquaporin-2 expression in principal cells of the CD. Accordingly, we hypothesized that activation of V2R increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 48 publications
2
36
0
Order By: Relevance
“…Our data suggest that PGE 2 may be the initial stimuli to promote prorenin-renin mediated stimulation of PRR and COX-2 augmentation in CD cells. Our data suggest that this stimulation is mediated by EP1 and EP4 receptors (Figure 5), which are linked to the stimulation of PKC-Ca2+ and stimulation of cAMP formation within the cell and both mechanisms seem to be involved in renin synthesis in the CD 23 . We previously showed that during the early phase of ANG II-dependent hypertension, membrane-bound PRR and COX-2 are augmented in the renal medullary tissues 12 .…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Our data suggest that PGE 2 may be the initial stimuli to promote prorenin-renin mediated stimulation of PRR and COX-2 augmentation in CD cells. Our data suggest that this stimulation is mediated by EP1 and EP4 receptors (Figure 5), which are linked to the stimulation of PKC-Ca2+ and stimulation of cAMP formation within the cell and both mechanisms seem to be involved in renin synthesis in the CD 23 . We previously showed that during the early phase of ANG II-dependent hypertension, membrane-bound PRR and COX-2 are augmented in the renal medullary tissues 12 .…”
Section: Discussionmentioning
confidence: 65%
“…It has been shown that M-1 CD cells express EP1, EP3, and EP4 17 . We have previously demonstrated that activation of the AT1 receptor increases prorenin and renin expression via cAMP accumulation, which is dependent on PKC activity 9,23 . In the MD, the activation of EP4 receptor enhances cAMP formation and activates the cAMP-CREB pathway and renin synthesis in JG cells 29 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AVP also stimulated release of prorenin, and sPRR in primary rat IMCD cells 56 . In M-1 CD cell line, a similar enhancement of renin mRNA, prorenin and renin is observed following desmopressin (ddAVP) treatment 57 . Together, the in vitro data demonstrates a potential role of PRR in mediating AVP-induced AQP2 expression in the CD cells.…”
Section: Prr Regulation Of Water Homeostasismentioning
confidence: 66%